Once again to the Question of the Title of A. S. Pushkin “the Sun of Russian Poetry” - I. V. Kudryashov (Научный диалог)
The article is devoted to the analysis of the figurative definition of the meaning of Pushkin as the “sun of Russian poetry” from a brief notice of the death of A. S. Pushkin, published on January 30, 1837 in the 5th issue of Literary Additions, an appendix to the newspaper “Russian Invalid”. It is noted that the informal title of “sun” of national literature Pushkin received during his life thanks to the critic V. G. Belinsky, who, in “Literary Dreams” (1834) was the first to make a figurative comparison of the influence of the poet of the 20s of the XIX century work, who was “supreme leader” in the literature of that time, on the development of Russian literature with the influence of the sun on earth and earthly life. The end of the “Pushkin period” proclaimed by Belinsky in “Literary Dreams” and the general desire of literary circles to create national idols served as the basis for Pushkin’s title in Russian criticism of 1834-1837. However, the numerous titles that article authors generously awarded Pushkin during his lifetime did not consolidate in the national consciousness as firmly as the “high title” given to the poet by Belinsky in “Literary Dreams”, thanks to the lifetime glory and love of the people for his poet, his national vitality and centrality in Russian culture at that time. The author of the article focuses on the fact that, in the light of this position, the figurative definition of Pushkin’s meaning “the sun of Russian poetry” used in the obituary by V. F. Odoevsky essentially reproduces the informal title of the great poet, already rooted in the national consciousness, as the “sun” of national literature, which was first of critics awarded to Pushkin by Belinsky.